2017
DOI: 10.1016/j.antiviral.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral lectins: Selective inhibitors of viral entry

Abstract: Many natural lectins have been reported to have antiviral activity. As some of these have been put forward as potential development candidates for preventing or treating viral infections, we have set out in this review to survey the literature on antiviral lectins. The review groups lectins by structural class and class of source organism we also detail their carbohydrate specificity and their reported antiviral activities. The review concludes with a brief discussion of several of the pertinent hurdles that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
149
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 157 publications
(328 reference statements)
1
149
0
10
Order By: Relevance
“…Monosaccharide residues of Gal, Man, Glc, Fuc, GalNAc, GlcNAc and NeuAc are represented by symbols as shown in the box. Figure 3, HRL40 exclusively bound to some of HM-glycans (11, 12, 14, 15, 17 and 18), and had no binding interaction with other sugar types; complex type N-glycans (1)(2)(3)(4)(5)(6)(7), an N-glycan core pentasaccharide (19), and oligosaccharides from glycolipids (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The binding preference of HRL40 for HM-glycans depended on the structure of branched oligomannosides; the highest binding activity was observed with oligosaccharides 11, 12 and 15 (binding activity, 100%), a little less binding activity with oligosaccharides 14 (89%) and 17 (74%), and moderate activity was with an -7), high-mannose type N-glycans (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), an N-glycan core pentasaccharide (19), and oligosaccharides originated from glycolipid (20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Oligosaccharide-binding Specificity Of Hrl40mentioning
confidence: 99%
See 1 more Smart Citation
“…Monosaccharide residues of Gal, Man, Glc, Fuc, GalNAc, GlcNAc and NeuAc are represented by symbols as shown in the box. Figure 3, HRL40 exclusively bound to some of HM-glycans (11, 12, 14, 15, 17 and 18), and had no binding interaction with other sugar types; complex type N-glycans (1)(2)(3)(4)(5)(6)(7), an N-glycan core pentasaccharide (19), and oligosaccharides from glycolipids (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The binding preference of HRL40 for HM-glycans depended on the structure of branched oligomannosides; the highest binding activity was observed with oligosaccharides 11, 12 and 15 (binding activity, 100%), a little less binding activity with oligosaccharides 14 (89%) and 17 (74%), and moderate activity was with an -7), high-mannose type N-glycans (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), an N-glycan core pentasaccharide (19), and oligosaccharides originated from glycolipid (20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Oligosaccharide-binding Specificity Of Hrl40mentioning
confidence: 99%
“…The oligosaccharide-binding property of HRL40 was examined by a centrifugal ultrafiltration-HPLC method [6,28] with a serial of pyridylaminated (PA-) oligosaccharides, including complex type N-glycans (1-7 in Figures 2 and 3), HM-glycans (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), an N-glycan core pentasaccharide (19), and oligosaccharides originated from glycolipids (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The schematic structures of oligosaccharides examined are shown in Figure 2.…”
Section: Oligosaccharide-binding Specificity Of Hrl40mentioning
confidence: 99%
“…Six consensus sequences from influenza NP, M1 and matrix 2 (M2) proteins were identified and synthesized into a candidate vaccine. Flu-v has been shown to induce a specific CD8 + response against these conserved epitopes and confer protection against heterotypic infection in mice [59], and a Phase Ib challenge trial also showed that the blood cells from immunized subjects exhibited cross reactive immunity against different influenza viruses [62,63].…”
Section: Epitope-peptide Based Vaccinesmentioning
confidence: 99%
“…Lectins are a unique and heterologous class of proteins with the ability to recognize and reversibly bind a variety of sugar structures present on the cell surface (Santos et al, 2014). They are found in a wide range of organisms, from viruses and bacteria to animals, plants, and humans (Mitchell et al, 2017). They have important biological functions in the organisms, including cell-cell interaction, protection from pathogens, cell adhesion, and intracellular translocation of glycoproteins, and they also act as storage proteins (Yamashita et al, 1999;Jiang et al, 2006;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%